Analisis Pengaruh Umur Harapan Hidup, Harapan Lama Sekolah, Rata-rata Lama Sekolah dan Tingkat Pengangguran Terbuka Terhadap Indeks Pembangunan Manusia Berdasarkan Kabupaten/Kota di Pulau Kalimantan Tahun 2022 - Prahasta , Kelvin Doni; Isnaniah , Ukhti Nurul; Nurlaily , Diana; Nurhayati, Farida; Silfiani , Mega (Jurusan Matematika dan Teknologi Informasi, 2023)
Human resources have an important role in creating development, namely development that aims to create a healthy community environment that can lead a productive life. This study aims to analyze the influence of Life Expectancy (UHH), Expected Years of Schooling (HLS), Average Years of Schooling (RLS) and Level of Open Disorders (TPT) on the Human Development Index (HDI) on Kalimantan Island. The data used in this research is secondary data obtained from BPS in all provinces on Kalimantan Island based on districts/cities. Data were processed using multiple linear regression analysis. The results of this research show that the determinant coefficient value obtained is 90.65% which means that the distribution of the human development index variable can be explained by the variables life expectancy, expected length of schooling, average length of schooling and the open poverty rate of 90.65%. The variable life expectancy has no effect and is not significant on the human development index on Kalimantan Island, the expected length of schooling variable has a positive and significant effect on the human development index on Kalimantan Island, the average length of schooling variable has a positive and significant effect on the human development index on Kalimantan Island and the open poverty level variable has a positive and significant effect on the human development index on Kalimantan Island